(untitled) (Journal of Educational Sciences, 2021)
This paper provides an account of an action-based study (Kemmis et al., 2014), which was conduct- ed with the purpose to develop teacher leadership in four schools in Kazakhstan. By drawing on a non- positional approach to teacher leadership (Frost et al., 2000), this study sought bottom-up approaches to educational reform, school leadership and professional development in schools in Kazakhstan. The nine-month intervention programme, which was called the Teacher Leadership for Learning and Col- laboration, introduced strategies and created conditions for teachers to lead educational improvement at classroom, school and system level. Teachers’ leadership projects had an impact on classroom and whole-school practices. The outcomes of this study indicate that there is a need for revisiting teachers’ professional roles in schools and transforming schools into a learning organisation. As such, educational reform and improvement requires building local capacity, which may involve creating conditions for leadership development and teacher empowerment within schools. Key words: teacher leadership development, school leadership, professional learning, school re- form, action-based research.